APLIKASI SKETSA GAMBAR DAN TULISAN PADA VIDEO CALL BERBASIS ANDROID - Anton Setiawan Honggowibowo; Asih Pujiastuti; Vendy Yuda Saputra (Compiler, 2017)
Video Call is a set of interactive telecommunication technologies which allow two parties of people in different locations can interact via two-way delivery of audio and video in real time. Tools to sketch pictures and writings on the application ViCall aims to facilitate educators do the learning process using media with video call implementation sketch pictures and writings as explanatory. Educators start doing sketches image and writings and then saved. After that upload sketches image and writings made by educators can then be shown to the students. The results of the testing of the application can be run on at least speksifikasi android kitkat v4.4.4. On testing provider obtained the average connection time 8.33 seconds. Based on a questionnaire, test this application generates 84.4% by criteria of "very good".